A Specialist's Quoted Depth and the Limit Order Book - Kavajecz, Kenneth A. (Journal of Finance, 1999)
By partitioning quoted depth into the specialist's contribution and the limit order book's contribution, the paper investigates whether specialists manage quoted depth to reduce adverse selection risk. The results show that both specialists and limit order traders reduce depth around information events, thereby reducing their exposure to adverse selection costs. Moreover, specialists' quotes may reflect only the limit order book on the side (or sides) of the market where they believe there is a chance of informed trading. Changes in quoted depth are consistent with specialists managing their inventory as well as having knowledge of the stock's future value.